GE_GERICHTE P/9800/2019 vom 9. November 2021 - GE Cour de justice (2021)
LÉSION CORPORELLE GRAVE;PEINE | CP.125; LCR.26; LCR.36.al4; LCR.39.al1.letb; LCR.39.al2; OCR.17.al4; OCR.28.al3; CP.47; CP.34.al2